Measurement of the J/ψ pair production cross-section in pp collisions at √s = 13 TeV - Aaij, R; Adeva, B; Adinolfi, M; Evans, T; Gandini, P; Gruberg Cazon, B; Hadavizadeh, T; Harnew, N; Hill, D; Jalocha, P; John, M; Jurik, N; et al. (Springer, 2017)
The production cross-section of J/ψ pairs is measured using a data sample of pp collisions collected by the LHCb experiment at a centre-of-mass energy of s=13 TeV, corresponding to an integrated luminosity of 279 ±11 pb −1 . The measurement is performed for J/ψ mesons with a transverse momentum of less than 10 GeV/c in the rapidity range 2.0 < y < 4.5. The production cross-section is measured to be 15.2 ± 1.0 ± 0.9 nb. The first uncertainty is statistical, and the second is systematic. The differential cross-sections as functions of several kinematic variables of the J/ψ pair are measured and compared to theoretical predictions.